Soil physical quality on conilon coffee intercropping and monoculture - Souza, Gustavo Soares de; Dan, Maurício Lima; Araújo, João Batista Silva (Coffee Science - ISSN 1984-3909, 2016)
The objective of this study was to evaluate the effects of conilon coffee the unshaded and shaded with tree species on soil physical quality. Six treatments were studied: T1- coffee monoculture; T2, T3, T4 and T5- intercropping coffee with peach palm, gliricidia, banana and inga, respectively; T6- native vegetation in natural regeneration. Soil samples were collected at a depth of 0-0.10 m for determination of soil attributes. Similar values of soil bulk density, total porosity, organic matter and carbon stocks occurred in the coffee monoculture and intercropping managements. T2 and T3 showed a greater plant-available water capacity, with 142 and 135 L m-3, which resulted in higher soil moisture. Lower aeration porosity occurred in T2 and T3. The treatments presented non-limiting S index (S>0.035), with the exception of T4. The treatments presented critical bulk density of 1.32 Mg m-3. The increase in soil organic matter resulted in an increase of the S index. The managements of the conilon coffee plantation with peach palm and gliricidia presented improvements in soil physical quality. The choice of species used in intercropping with conilon coffee must be adjusted to the characteristics of the region and the farmer.